Respuesta :

Answer:

Step-by-step explanation:

23) a) n - (n+1)

Remove the parenthesis by multiplying (n+1) by (-1)

n - (n+1) = n - n - 1 = -1

b) n(n+1) = n*n + n*1

              = n² + n

c) When we are adding the two numbers it is,

n² + n - 1. This will always be odd because n² + n will always be even and when we subtract 1 from that it will be odd

Example: Take n = 3

n² + n =  3*3 + 3 = 9 + 3 =12; So, n² + n -1 = 12- 1 =11 --> odd

When n = 7

n² + n = 49 + 7 = 56 ; So, n² + n -1 = 56-1 = 55 ---> odd

When n =8

n² + n = 64 + 8 = 72;  So, n² + n -1 = 72 -1 = 71

When n = 16

n² + n = 256 +16 = 272 ; So, n² + n - 1 = 272 - 1 = 271 ----->odd

ACCESS MORE